Transhumanism (h+) vis-à-vis African Holism - Robert Falconer (African Theological Journal for Church and Society, 2023)
Transhumanism (h+) is a social and philosophical movement that looks to enhance human cognitive and physiological conditions by developing technology to improve human health and extend human life, leading up to a digital version of eternal life on a virtual platform. Considerable research from neuroscience, technology, the sciences, philosophy, and ethics has been ploughed into Transhumanism and related fields. Although there are some Christian voices from the west, like Fazale Rana and John Lennox, there are few Christian voices from Africa addressing the Transhumanist concern. The traditional African philosophy of holism together with a theological-biblical response may help us identify the dangers of this movement. The research findings provide a framework for constructing a teleological ethic for an emerging Transhumanist context in Africa. The paper employs a modified Architectonic Theology as its research methodology which includes the following: (1) Exploring the Transhumanist project, both historical and present. (2) Exploring the traditional African philosophy of holism in relationship to Transhumanism, (3) exploring Christian theology in response to Transhumanism, and (4) constructing a teleological ethic for Transhumanism given African holism and the theological-biblical response. The significance of this paper empowers African Christianity with a theological-biblical response to the emerging Transhumanist project that is not only contextual to African thought but relevant for all. Furthermore, it gives Africa a critical voice in a global movement.